Impact of Increasing Comorbidity Burden on Resource Utilization in Patients With Proximal Humerus Fractures. Issue 21 (1st November 2020) - London, Daniel A.; Cagle, Paul J.; Parsons, Bradford O.; Galatz, Leesa M.; Anthony, Shawn G.; Zubizarreta, Nicole; Mazumdar, Madhu; Poeran, Jashvant
Abstract : Introduction: Proximal humerus fractures (PHF) are a common upper extremity fracture in the elderly cohort. An aging and more comorbid cohort, along with recent trends of increased operative intervention, suggests that there could be an increase in resource utilization caring for these patients. We sought to quantify these trends and quantify the impact that comorbidity burden has on resource utilization. Methods: Data on 83, 975 patients with PHFs were included from the Premier Healthcare Claims database (2006 to 2016) and stratified by Deyo-Charlson index. Multivariable models assessed associations between Deyo-Charlson comorbidities and resource utilization (length and cost of hospitalization, and opioid utilization in oral morphine equivalents [OME]) for five treatment modalities: (1) open reduction internal fixation (ORIF), (2) closed reduction internal fixation (CRIF), (3) hemiarthroplasty, (4) reverse total shoulder arthroplasty, and (5) nonsurgical treatment (NST). We report a percentage change in resource utilization associated with an increasing comorbidity burden. Results: Overall distribution of treatment modalities was (proportion in percent/median length of stay/cost/opioid utilization): ORIF (19.1%/2 days/$11, 183/210 OME), CRIF (1.1%/4 days/$11, 139/220 OME), hemiarthroplasty (10.7%/3 days/$17, 255/275 OME), reverse total shoulder arthroplasty (6.4%/3 days/$21, 486/230 OME), and NST (62.7%/0 days/$1, 269/30 OME). Patients with an increased comorbidity burden showed a pattern of (1) more pronounced relative increases in length of stay among those treated operatively (65.0% for patients with a Deyo-Charlson index >2), whereas (2) increases in cost of hospitalization (60.1%) and opioid utilization (37.0%) were more pronounced in the NST group. Discussion: In patients with PHFs, increased comorbidity burden coincides with substantial increases in resource utilization in patients receiving surgical and NSTs. Combined with known increases in operative intervention, trends in increased comorbidity burden may have profound effects on the cohort level and resource utilization for those with PHFs, especially because the use of bundled payment strategies for fractures increases. Level of Evidence: Level III